Factors Associated with the Incidence of Obesity in Women of Childbearing Age at Bandar Khalifah Health Center - Ika Nur Saputri (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Nutritional problems are one of the challenges in the field of public health in Indonesia, both related to malnutrition and excess nutrition. Changes in the era that drive economic progress also affect food consumption patterns, which ultimately contribute to the increase in obesity cases. Obesity is a significant health issue in the era of globalization and is defined as a condition in which there is an abnormal increase in body fat levels, as well as a decrease in muscle mass, quality, and strength. Women of childbearing age (WUS) are a group of women who are in the transition phase from late adolescence to early adulthood, marked by the onset of menstruation and the development of reproductive organs until reaching peak fertility. This period is a stage in a woman's life cycle that involves physical and psychological growth and development in the age range of 18-40 years. This study used an analytical observational method with a cross-sectional study design, where a survey was conducted to collect data through a questionnaire. The results of the univariate analysis of 91 respondents showed that 85.7% were obese, while 14.3% were not. Most respondents (84.6%) often consumed fast food, and 57.1% had low levels of physical activity. In terms of knowledge, 82.4% of respondents who are obese have a low level of knowledge, and most of them (54.9%) are housewives who do not have jobs. Thus, factors related to the incidence of obesity in women of childbearing age include fast food consumption patterns, physical activity levels, and knowledge levels.